Answer:
17
Step-by-step explanation:
you said that in the problem lol
Answer:
12x-2
Step-by-step explanation:
You need to add 5x+1 and 7x-3.
5x+1+7x-3.
We need to organize this into common terms.
5x+7x+1-3
Now we simplify.
12x-2
That is the final answer!!
Hope this helped!!!! :D
Answer:
<h3> f^−1(x) = x + 7</h3>
Step-by-step explanation:
Replace f(x) with y. y = x − 7
Interchange the variables. x = y − 7
Solve for y. y = x + 7
Solve for y and replace with f^−1 (x). f^−1(x) = x + 7
I hope this helps have a great day :)
Answer:
it has to be a or d
Step-by-step explanation:
they have 4000 in 1996 but we want 1991.so we get 15 percent of least time but i belive its d